PENINGKATAN KUALITAS HUNIAN PADA PERMUKIMAN PADAT DI RW 02, KELURAHAN KRENDANG, JAKARTA BARAT: - - Widiarso, Tulus Widiarso; Karista, Ardilla Jefri; Rintawati, Dewi (Universitas Trisakti, 2024)
The settlement in RW 02, Krendang sub-district, Tambora district, West Jakarta, is a dense and unorganized urban settlement resulting from an unplanned incremental growth process. Apart from poor environmental sanitation conditions, this settlement has a low quality of residential space with very limited natural lighting and ventilation due to the closeness of the buildings and the lack of open space. This settlement is the location for implementing a community service program which aims to help the West Jakarta government deal with the city's slum problem by involving community participation to improve the quality of residential space. The initial program in 2023 aims to open people's minds about the importance of healthy residential spaces, and to make this happen can be done using simple, low-cost methods. In the next stage, sustainable programs will be continued until a model of healthy, low-cost housing is realized in this settlement. A series of community service activities have been carried out with the culmination of counseling activities for social treatment to build collective insight and awareness among residents. The counseling took place at the community hall, attended by RW administrators as well as RT representatives and community leaders within RW 02. The counselor team used pictures of simulation designs for the renovation of multi-purpose buildings and pre-school children's education in RW 02 as counseling aids. Based on pre-test and post-test data through filling out questionnaires by participants, it shows a significant increase in collective awareness regarding the program objectives.